Advances in the prognosis of soil salinization and sodification for sustainable soil and water management - SENTÍS, ILDEFONSO PLA; ARORA, SANJAY (Journal of Soil and Water Conservation, 2025)
Soil and water resources resource are submitted to increasing pressure under global change effects, frequently resulting in widespread soil and water degradation processes, including soil salinization and sodification. Salt-affected soils, both saline and sodic, may develop both under dryland and irrigated conditions, with negative consequences in the environment, in the crop production and in the animal and human health. In both of them hydrological processes are involved in their development, but in the case of sodic soils we have to consider some additional chemical and physicochemical reactions. This is especially true where we have to include the effects of the groundwater level and composition. Both the addition of irrigation water and the changes in depth and composition of groundwater, may cause great changes in the water and solute balances in the soil profile. There is proposed the use of an hydrological and hydro-geochemical modeling approach, which has been developed through successive approximations and validations under very different conditions, for the diagnosis and prediction of such changes, and for the selection of the best practices and systems of irrigation and drainage for a more efficient use of irrigation water, reducing the losses and contamination of surface and groundwater, and controlling the soil salinization and sodification. There is presented an adaptation of the model SALSODIMAR, including new specific hydrological components of the water and solute balances, to make it useful to predict the processes of both the dryland salinization and sodification processes originated by groundwater, and the combined effects of irrigation and groundwater, with or without vegetation, under different climate conditions.